Analisis Pengaruh Profitabilitas, Struktur Aktiva Dan Likuiditas Terhadap Struktur Modal Perusahaan Industri Tekstil Dan Garment Yang Terdaftar Di Bursa Efek Indonesia (BEI) - Ni Kadek Dila Ardianingsih; Ni Wayan Suartini; I Nyoman Gede Supraptha (MENAWAN : Jurnal Riset dan Publikasi Ilmu Ekonomi, 2023)
This research was carried out on industrial companies on the Indonesian Stock Exchange (IDX) with the title "Analysis of the influence of profitability, asset structure and liquidity on the capital structure of textile and garment industrial companies listed on the IDX". This research uses quantitative data with secondary data sources. This research uses methodspurposive sampling, The sample data in this research is 18 samples from the 2019-2021 period. This research uses multiple linear analysis techniques, partially this research states that 1) Profitability has a significant effect on capital structure, 2) Asset structure has a significant effect on capital structure, 3) Liquidity has a significant effect on capital structure, 4) profitability, structure assets and liquidity together (simultaneously) have a significant effect on capital structure. In the determination test it was found that the magnitude of the influence of profitability, asset structure and liquidity on capital structure was 93.6%, while it was 6.4% (100% - 93 .6%) is influenced by other factors on the capital structure of companies in the Textile and Garment Sub-Sector Industry for the 2019-2021 period, explained by variables outside the independent variables of this research.